Design optimization and trajectory planning of a strawberry harvesting manipulator - Saoud, Inas; Jaafari, Hatim Idriss; Chahboun, Asaad; Raissouni, Naoufal; Achhab, Nizar Ben; Azyat, Abdelilah (Bulletin of Electrical Engineering and Informatics, 2024)
This paper presents a systematic approach to optimizing the structural parameters of a 4-degree-of-freedom (DoF) strawberry harvesting manipulator to minimize its workspace. Unlike previous research that primarily concentrated on the spatial needs related to fruit distribution areas, this work addresses the spatial dynamics of different stages of the fruit-picking process. This is achieved by combining the workspace model method, mathematical modeling, and the GlobalSearch algorithm in the optimization process. A comprehensive verification was conducted using the Denavit-Hartenberg method to simulate the workspace of the optimal manipulator structure. This ensured that the manipulator effectively covered the entire harvesting space. The research design involves exploring an optimal trajectory planning method by adopting a modified sine jerk profile that minimizes overall trajectory duration while maintaining good smoothness. The effectiveness of this method is demonstrated through a simulation of the trajectory of the four joints to drive the end effector from the initial position to the position of the strawberry. This approach yields execution times up to 27% shorter than in previous studies. The proposed method is useful for optimizing the physical and trajectory design of the harvesting manipulator that operates in confined and restricted environments to enhance efficiency, adaptability, and safety in harvesting operations.